Factors Associated with Unwanted Pregnancy among Adolescent Women Receiving Prenatal Care at Krathumbaen Hospital, Samut Sakhon Province - Chuenkitiyanon, Somrudee; Jantanakul, Pichaporn (Journal of Nursing, Siam University, 2021)
This descriptive study aimed to examine impacts of pregnancy and factors affecting pregnancy among teen mothers. Participants were 140 teen mothers aged 11-19 who visited antenatal care unit at Krathumbaen hospital from July 2019 to August 2020. The purpose of this research was to explore the relationship between family relationship sexual values and its associated factors including effects of pregnancy on mental health, self-care, supports from family, and needs of teen mothers. The sample including 140 unplanned adolescent pregnant woman attending antenatal care clinics at Krathumbaen hospital. They were selected through purposive random sampling. Research instruments consisted of the sexual values pregnancy questionnaire, the family support pregnancy questionnaire. Data was collected during July and August 2019 and analyzed by using descriptive statistics and Pearson’s product moment correlation. This study suggests that pregnancy affected mental health of teen mothers, and family should be encouraged to provide psychological and practical support for teen mothers. Both family and educational institution have an important role to provide the right value, encourage the good attitude to sexual relations and knowledge of family planning.